A New Estimation Method for Rotor Size of UAV Based on Peak Time-Shift Effect in Micro-Doppler Lidar - Zhang, Yong; Li, Dongmei; Han, Yi; Yang, Zhen; Dai, Xin; Guo, Xinmin; Zhang, Jianlong (Frontiers in Physics, 2022)
To solve the problem that the existing identification parameters of rotor unmanned aerial vehicle (UAV) are few and limited by the detection mode, an identification method for estimating rotor blade width based on the peak time-shift effect is proposed for the first time. Taking the width of the rotor blade as the parameter to identify rotor of UAV, the time-shift effect and its relationship with rotor blade width are verified by theoretical analysis and simulation. The proposed time-shift method has the characteristics of high-precision extraction of rotor width and its effectiveness is verified by simulation and experiments. The aspect ratio of the rotor is accurately extracted based on the proposed time-shift method under the condition of an unknown pitch angle. Simulation results show that the estimation accuracy of width and aspect ratio are up to 98% and 98.4%. The experimental results show that the relative errors of width and aspect ratio are less than 7% and 4%, respectively. This study provides the theoretical basis and technical support for the high accuracy identification of rotorcraft UAVs.